2014
DOI: 10.4037/ccn2014951
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Patients’ Readiness for Coronary Artery Bypass Graft Surgery

Abstract: Background Preoperative interventions improve outcomes for patients after coronary artery bypass surgery (CABG). Objective To reduce mortality for patients undergoing urgent CABG. Methods Eight centers implemented preoperative aspirin and statin, preinduction heart rate less than 80/min, hematocrit greater than 30%, blood sugar less than 150 mg/dL (8.3 mmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To date, while studies have mainly focused on postoperative functional performance and recovery (10), there is increasing evidence that preoperative readiness is essential for successful postoperative recovery. In particular, patient readiness for surgery has been associated with shorter mechanical intubation times and reduced length of stay after CABG (24). Preoperative frailty is also an important indicator in preoperative decision-making and can help predict patient recovery trajectory (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, while studies have mainly focused on postoperative functional performance and recovery (10), there is increasing evidence that preoperative readiness is essential for successful postoperative recovery. In particular, patient readiness for surgery has been associated with shorter mechanical intubation times and reduced length of stay after CABG (24). Preoperative frailty is also an important indicator in preoperative decision-making and can help predict patient recovery trajectory (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, significant heterogeneity among studies was noted in both meta-analyses [44,70]. Further, a recently published study showed that a bundle of preoperative interventions, including PST, before urgent CABG improved outcomes, including shorter hospital stays and lesser intubation times [71]. This effect can be explained by the reduction in the rate of postoperative complications as detailed previously.…”
Section: Preoperative Statin Therapy and Length Of Hospital Staymentioning
confidence: 93%
“…In addition, with advances in perioperative management, we have shifted quality improvement efforts to best practices in the areas of perioperative readiness for surgery, reduction of PRBC transfusion, and development of prediction models for low-output heart failure. 21,22 We have maintained momentum for the NNECDSG by continuously evolving our quality improvement initiatives, data collection methods, and surgeon-specific quality reports.…”
Section: Commentmentioning
confidence: 99%